ANALYSIS OF HUMAN RESOURCES MANAGEMENT IN THE NEW NORMAL ERA TO DEVELOP LEARNING STRATEGIES - Finny Redjeki (Jurnal Kelola: Jurnal Ilmu Sosial, 2021)
The sudden emergence of the Covid-19 virus has caused changes in various aspects of our lives. These changes then lead to a new rule that needs to be followed by everyone, so this situation is referred to as the new normal. Human resource management has a vital role in life in the new normal and oversees various associations or institutions. In dealing with the new normal, various learning activities need to be changed so that the spread of the Covid-19 virus can be stopped or inhibited. Human resource management that oversees educational institutions needs to find new learning strategies. This research was carried out using a qualitative approach with secondary data sources. The study results indicate that the implementation of virtual learning guided by the teacher needs to be carried out with careful efforts, preparation, and debriefing to reduce errors that occur. Then, on the other hand, parents need to help and supervise their children in learning so that there is no laziness or cheating during exams at home. Through the role of teachers and parents, the value in the academic world can be upheld, so this strategy is considered appropriate in this new normal era.